Cu-catalyzed cross-coupling reactions of vinyl epoxide with organoboron compounds: access to homoallylic alcohols. Issue 72 (12th December 2018) - Lu, Xiao-Yu; Li, Jin-Song; Wang, Jin-Yu; Wang, Shi-Qun; Li, Yue-Ming; Zhu, Yu-Jing; Zhou, Ran; Ma, Wen-Jing
Abstract : Copper-catalyzed cross-coupling reactions of vinyl epoxide with arylboronates to obtain aryl-substituted homoallylic alcohols are described. Abstract : Copper-catalyzed cross-coupling reactions of vinyl epoxide with arylboronates to obtain aryl-substituted homoallylic alcohols are described. The reaction selectivity was different to that of previously reported vinyl epoxide ring-opening reactions using aryl nucleophiles. The reaction proceeded under mild conditions, affording aryl-substituted homoallylic alcohols with high selectivity and in good to excellent yields. The reaction provides convenient access to aryl-substituted homoallylic alcohols from vinyl epoxide